Coping Strategies of Older American Korean War Veterans: A Mixed Research Study. Issue 3 (3rd July 2017) - Lee, Heesoon; Holden, Brett E.; Adams, Peggy; Mason, Derek
ABSTRACT: For American Korean War veterans, military service during wartime is a major life-changing experience across their lifespan. Research on them, while they are still living, is critical to understanding how older veterans have dealt with social adjustment after the war and in their later lives. This study examined the impact of military experience and social support upon coping strategies of older veterans. Both surveys and focus groups were conducted to collect data from 20 American Korean War veterans and 22 older non-veterans. Our findings indicate that the American Korean War Veterans Association has been a critical source of social support for veteran participants, leading them into more adaptive coping strategies. Focusing upon positive adaptation after traumatic events is a recommended shift of practice for helping professionals. More implications of the activity professionals were discussed.